Tri-band absorption enhancement in monolayer graphene in visible spectrum due to multiple plasmon resonances in metal–insulator–metal nanostructure. (20th June 2018) - Liu, Bo; Tang, Chaojun; Chen, Jing; Xie, Ningyan; Zheng, Long; Wang, Shuai
Abstract: Suspended graphene has a very low light-absorption efficiency, of approximately 2.3% from the visible to near-infrared region, which is defined by the fine-structure constant. For many applications in optoelectronic devices (e.g., photodetectors), light-absorption enhancement in graphene is desired. We numerically investigate a tri-band absorption enhancement in graphene at optical frequencies, resulting from the excitations of multiple electric and magnetic plasmon modes in a metal–insulator–metal nanostructure. The position of this tri-band absorption enhancement can be easily controlled by tuning the resonance wavelengths of the plasmon modes.